Analisis Potensi Penghimpunan Zakat ASN di Kota Depok Menggunakan Pendekatan SWOT - Asma Nur Adilah; Rio Erismen Armen (Al Maal: Journal of Islamic Economics and Banking, 2022)
The study aims to examine the potential of zakat that is collected from public servants (called as Aparatur Sipil Negara or ASN) in Depok, West Java, by using the SWOT approach. This is essential based on ijtihad of several contemporary Shari’ah scholars who obliged zakat on salary earned from any professions/jobs (including ASN) when meets the requirements of zakat (nishab and haul). In a preliminary study, the potential for zakat of ASN in Depok was identified to be reaching 1-1,5 billion rupiah per-month, but only about 30% of it has been achieved. The method used in this study is descriptive qualitative by using primary and secondary data. Primary data are obtained through interviews with a number of ASN and BAZNAS of Depok. Whilst, secondary data are obtained from various literatures such as books, journals, magazines, articles, reports, and previous studies. The collected data are narrated and analyzed by using the SWOT approach. The study identified a number of factors causing a wide gap between the potential and ASN’s zakat achievement in Depok. Among the factors are the less understanding of zakat on salary, the high of living cost in Depok, uneven socialization and marketing of zakat collection, the absence of regulations forcing zakat on salary, and the existence of several zakat institutions other than BAZNAS in Depok.